In Vitro Propagation of Tribulus terrestris with IAA and BAP Concentrations - Samanhudi Samanhudi; Ahmad Yunus; Rahmanto Rahmanto (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2021)
Tribulus terrestris is conventionally propagated using seeds but has limited germination capacity. One approach that can be done for this plant multiplication is in vitro tissue culture. This study was conducted to determine the growth potential of T. terrestris in vitro by the addition of auxin (IAA) and cytokinin (BAP) as growth regulators at several concentrations. The study was conducted at the Laboratory of Plant Physiology and Biotechnology, Faculty of Agriculture, Universitas Sebelas Maret Surakarta from February to December 2017. The experiment employed factorial Completely Randomized Design (CRD) method with 2 factors, namely IAA concentration (0 ppm, 0.1 ppm, 0.2 ppm, 0.3 ppm), and BAP concentration (0 ppm, 0.3 ppm, 0.5 ppm, 0.7 ppm). The observed growth parameters were shoot emergence time, leaf emergence time, root emergence time, number of leaves, and number of roots. Data were analyzed using analysis of variance followed by DMRT with a 95% confidence level. The results showed that the addition of IAA only affects leaf emergence time, while the addition of BAP had a significant effect on the leaf emergence time and number of leaves. The interactions between IAA and BAP had a significant effect on leaf emergence time. Keywords: explant; plant growth; tissue culture.